Implicações psicossociais da participação de estudantes no Movimento Secundarista Autônomo de São Paulo - Purin, Gláucia Tais (2020)
The present work deals with the theme of resistance, violence and suffering of students who participated in the Autonomous High School Students Movement of São Paulo. It aimed to analyze the psychosocial implications of the participation of students from São Paulo in the autonomous high school students movement in São Paulo, after the occupations in 2015. This research presents its social relevance anchored in 4 complementary elements: registration of the investigated phenomenon; visibility of the abused population; scientific-political denunciation and possible theoretical and practical subsidies related to the central theme. The method used was participatory research, carried out for 3 years with monitoring of the activities of high school students, in: assemblies, meetings, street demonstrations, public hearings, public classes, symposium in congress, moments of socialization and relaxation, all recorded in a diary field. Individual interviews were also conducted with three participants from the high school movement. The theoretical reference used is socio-historical psychology, based on the reflections of Vigotski and Lane on the understanding of subjectivity, Espinosa on the understanding of affections, and Sawaia on the proposal of the social exclusion/inclusion dialectic and ethical-political suffering. It was possible to analyze that students experience the social exclusion / inclusion dialectic and the ethical-political suffering, daily and subtly, due to the inequalities and violence imposed on them. After the occupations, high school students began to suffer police violence and violence in the school environment more frequently and intensely, starting to be attacked, watched, humiliated, despised, disqualified, ridiculed, politically persecuted, delegitimized, and criminalized. But, at the same time, they also experience a feeling of common and hope/utopia that motivates them to act with others and face forms of servitude and superstition. At MAS-SP they had good encounters that increased their power of action. They experienced dignity, respect, appreciation, cooperation, and the legitimacy to think, decide and act collectively in actions